The lost ticket - Sampson, Freya (Berkley, 2022)
"Strangers on a London bus unite to help an elderly man find his missed love connection in the heartwarming new novel from the acclaimed author of The Last Chance Library. When Libby Nicholls arrives in London, brokenhearted and with her life in tatters, the first person she meets on the bus is elderly Frank. He tells her about the time in 1962 that he met a girl on the number 88 bus, with beautiful red hair just like hers. They made plans for a date at the National Gallery art museum, but Frank lost the bus ticket with her number on it. For the past sixty years, he's ridden the same bus trying to find her, but with no luck. Libby is inspired to action and, with the help of an unlikely companion, she papers the bus route with posters advertising their search. Libby begins to open her guarded heart to new friendships and a budding romance as her tightly controlled world expands. But with Frank's dementia progressing quickly, their chance of finding the girl from the 88 bus is slipping away. More than anything, Libby wants Frank to see his lost love one more time. But their quest also shows Libby just how important it is to embrace her own chances for happiness--before it's too late--in a beautifully uplifting novel about how a shared common experience among strangers can transform lives in the most marvelous ways"--